Mortada Motahari and his role in renewing Islamic thought - boukhari, meriem; akake, abdelghani (Journal of Social Sciences and Humanities, 2024)
This research deals with the issue of renewing Islamic thought and reviving it by Mortada Motahari as one of the flags of contemporary Islamic thought, who was able to play thankful roles in the field of religious intellectual rooting, according to a militant experience that I included in the whole of the renewers, as he sought to invigorate the nation, and purify ideas from deposits Exotic deviations from authentic Islam, and presenting Islam as an integrated system of life in a modern way that responds to the requirements of reality, and thus the aim of this research was to show the extent of Mortada Motahari’s contributions to the revival of contemporary Islamic thought, relying in this on the critical analytical method as I deliberately collected the scattered of his views And his words, then analyze them in order to get acquainted with his efforts and extract what can be learned, as for the results, they included, in their entirety, the dismissal of specialized researchers to take an interest in the question of renewal, and work in studying reform experiences and on the approach of modernists and thinkers to get to know and understand them, so that they may find what contributes to solving some crises in which humanity is floundering in our time.